గౌతమ బుద్ధుడు - జవహర్లాల్ - Rao, Devulapalli Ramanuja (Andhra Saraswata Parishath, 1983)
This book is about speeches about Gowthama Budha and Jawaharlal Nehru
Gowthama Buddhudu - Jawaharalal
Keywords: Telugu; Literature; Telugu; Telugu